Health workers' perspectives on barriers and facilitators to implementing a new national cervical cancer screening program in Ethiopia - Breanne E. Lott; Atota Halkiyo; Dawit Worku Kassa; Tesfaye Kebede; Abdulkerim Dedefo; John Ehiri; Purnima Madhivanan; Scott Carvajal; Amr Soliman (BMC, 2021)
Abstract Background Cervical cancer disproportionately affects women in sub-Saharan Africa, compared with other world regions. In Ethiopia, a National Cancer Control Plan published in 2015, outlines an ambitious strategy to reduce the incidence and mortality of cervical cancer. This strategy includes widespread screening using visual inspection with acetic acid (VIA). As the national screening program has rolled out, there has been limited inquiry of provider experiences. This study aims to describe cancer control experts' perspectives regarding the cancer control strategy and implementation of VIA. Methods Semi-structured interviews with 18 participants elicited provider perspectives on cervical cancer prevention and screening. Open-ended interview questions queried barriers and facilitators to implementation of a new national screening program. Responses were analyzed using thematic analysis and mapped to the Integrated Behavioral Model. Participants were health providers and administrators with positionality as cancer control experts including screening program professionals, oncologists, and cancer focal persons at town, zone, and federal health offices at eleven government facilities in the Arsi, Bale, and Shoa zones of the Oromia region, and in the capital Addis Ababa. Results The cancer control plan and screening method, VIA, were described by participants as contextually appropriate and responsive to the unique service delivery challenges in Ethiopia. Screening implementation barriers included low community- and provider-awareness of cervical cancer and screening, lack of space and infrastructure to establish the screening center, lack of materials including cryotherapy machines for the "screen-and-treat" approach, and human resource issues such as high-turnover of staff and administration. Participant-generated solutions included additional training for providers, demand creation to increase patient flow through mass media campaigns, decentralization of screening from large regional hospitals to local health centers, improved monitoring and evaluation, and incentivization of screening services to motivate health providers. Conclusions As the Ethiopian government refines its Cancer Control Plan and scales up screening service implementation throughout the country, the findings from this study can inform the policies and practices of cervical cancer screening. Provider perspectives of barriers and facilitators to effective cancer control and screening implementation reveal areas for continued improvement such as provider training and coordination and collaboration in the health system.